Levels of microRNA miR-16 and miR-155 are altered in serum of patients with tuberculosis and associate with responses to therapy. (January 2017) - Wagh, Vishal; Urhekar, Anant; Modi, Deepak
Abstract: Identification of blood biomarkers that can be useful for predicting Mycobacterium tuberculosis (M.TB) infection, effect of therapy and Multi Drug Resistant (MDR) TB infected individuals is clinically useful for combating tuberculosis epidemic. In this study, we have evaluated the levels of selected miRNAs in serum of TB and MDR TB patients. In addition, we have studied their levels in serum of patients post-therapy. The levels of 4-miRNAs (miR-16, miR-29a, miR-125b and miR-155) were measured in 30 newly diagnosed TB patients, 19 Multi Drug Resistant (MDR) TB patients, 10 patients who completed TB therapy and were TB negative. 30 healthy individuals were recruited as controls. The levels of the miRNAs were estimated by qRT-PCR. Of the four miRNAs studied, the levels of miR-16 were significantly elevated and miR-155 were significantly reduced in serum of TB patients as compared to uninfected controls. The Receiver Operating Characteristic (ROC) curve of miR-16 and miR-155 exhibited a significant distinguishing efficiency with an AUC value of 1 (95% CI, 1 to 1) and 0.967 (95% CI, 0.92–1.04) respectively. Following the therapy, the levels of miR-16 and miR-155 returned to those observed in healthy subjects. In patients with MDR TB, miR-155 was lower as compared to healthy controls and TB treated group but higher as compared to TB naïve patients. miR-16 levels were lowest in serum of MDR TB patients compared to TB naïve, TB treated group and healthy controls. In conclusion, miR-16 and miR-155 in serum may act as surrogate biomarker for studying TB infection, progression of therapy and MDR TB.